State and Prospects of the Securities Market in the Developing Economy (on the Example of Kazakhstan) - KULBOSYNOVNA, Nurasheva Kulyanda; ASKARBEKOVNA, Kulanova Darikul; IMANBAEVNA, Abdikerimova Gulzhanar; TOIMAKHAMBETOVNA, Mergenbayeva Aziza (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The purpose of the research is to study the economic environment and determine the possibilities of issuing and circulating municipal bonds. The methods used were information sampling, its grouping, system and statistical analysis, comparison of indicators and logical conclusions. It has been determined that the large quasi-public sector, the feebleness of development institutions, the instability of the banking sector, and the uneven development of regions impede the formation of the stock market. Low household incomes, inflation and depreciation of the national currency reduce investment opportunities. The risks of buying securities by the population are not calculated, there are no clear guarantees for the rights of ordinary shareholders, the return of funds causes problems due to imperfect legislation. In order to substantiate the true opportunities and desires of people to spend money on the purchase of securities, questionnaires and interviews were conducted among representatives of various social groups. The study showed that citizens are willing to buy bonds, but first it is needed to create an innovative economy and implement attractive projects in the regions for the population in order to fully launch the stock market. In the current scheme for issuing municipal bonds, only the quasi-public sector is involved. To attract the investments from pension funds, insurance companies, small investors (population), the authors recommend a scheme of business processes for issuing and circulating bonds. The problems and proposals discussed are of interest to post-Soviet countries, which are facing with the need to develop the stock market.